Dampak Banjir pada Lahan Sawah terhadap Pendapatan Usahatani Padi di Desa Ibul Besar I Kecamatan Pemulutan Kabupaten Ogan Ilir - Muharrami Hanifah; Nurilla E Putri (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Hanifah M, Putri NE. 2022. Impact of flood on rice business income in Ibul Besar I Village Pemulutan District Ogan Ilir Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 562-571. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The flood that occurred became a problem in Ibul Besar I Village, Pemulutan District, Ogan Ilir Regency. Because of the flood it giving effect on crop and the cost of production of agriculture. The flood will impact on the land and the income of the farmers. This study aimed to (1) analyze the income of rice farmers before and after the flood, and (2) Analyze the impact of flooding on the income of rice farmers. This research was took place at Ibul Besar I Village. The research was accoured in July 2022. The research method used was a survey method. The results showed that (1) the average income received by farmers before the flood was 11,526,466.-IDR/lg/year while the average income of farmers after the flood was 9,886,800.-IDR/lg/year. The difference in income was 1,639,666.-IDR/lg/year, (3) The impact of flooding on farmers income in Ibul Besar I Village, it can be seen from five indicators, it was found that livelihood indicators are influential with a percentage of 68%. The farming indicator has no effect with a percentage of 38%. Productivity indicators have no effect with a percentage of 39%. The expense indicator has an effect with a percentage of 73%. Welfare indicators have an effect with a percentage of 67%.